Hey Mates!
( 6,6 ) ( h,0 ) ( 0, k ) are collinear then find 1/h + 1/k
Disclaimer - No irrelevant answers.
siddhartharao77:
is it 1/6?
Answers
Answered by
36
Let the given points be A(6,6), B(h,0) and C(0,k).
Here x1 = 6 and y1 = 6,
x2 = h and y2 = 0
x3 = 0 and y3 = k.
We know that Slope a line m = y2 - y1/x2 - x1.
Slope of AB:
(x1,y1) = (6,6) and (x2,y2) = (h,0).
![= \ \textgreater \ \frac{0 - 6}{h - 6} = \ \textgreater \ \frac{0 - 6}{h - 6}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B0+-+6%7D%7Bh+-+6%7D+)
![= \ \textgreater \ \frac{-6}{h - 6} = \ \textgreater \ \frac{-6}{h - 6}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B-6%7D%7Bh+-+6%7D+)
Slope of BC:
(x1,y1) = (h,0) and (x2,y2) = (0,k).
![= \ \textgreater \ m = \frac{k - 0}{0 - h} = \ \textgreater \ m = \frac{k - 0}{0 - h}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+m+%3D+%5Cfrac%7Bk+-+0%7D%7B0+-+h%7D+)
![= \ \textgreater \ m = \frac{k}{-h} = \ \textgreater \ m = \frac{k}{-h}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+m+%3D+%5Cfrac%7Bk%7D%7B-h%7D+)
Now,
Slope of AB = slope of BC
![= \ \textgreater \ \frac{-6}{h-6} = \frac{k}{-h} = \ \textgreater \ \frac{-6}{h-6} = \frac{k}{-h}](https://tex.z-dn.net/?f=+%3D+%5C+%5Ctextgreater+%5C++%5Cfrac%7B-6%7D%7Bh-6%7D+%3D++%5Cfrac%7Bk%7D%7B-h%7D+)
![= \ \textgreater \ 6h = kh - 6k = \ \textgreater \ 6h = kh - 6k](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++6h+%3D+kh+-+6k)
![= \ \textgreater \ 6h + 6k = kh = \ \textgreater \ 6h + 6k = kh](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++6h+%2B+6k+%3D+kh)
![= \ \textgreater \ 6(h + k) = kh = \ \textgreater \ 6(h + k) = kh](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++6%28h+%2B+k%29+%3D+kh)
![\frac{1}{h} + \frac{1}{k} = \frac{1}{6} \frac{1}{h} + \frac{1}{k} = \frac{1}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bh%7D+%2B++%5Cfrac%7B1%7D%7Bk%7D+%3D++%5Cfrac%7B1%7D%7B6%7D+)
Hope this helps!
Here x1 = 6 and y1 = 6,
x2 = h and y2 = 0
x3 = 0 and y3 = k.
We know that Slope a line m = y2 - y1/x2 - x1.
Slope of AB:
(x1,y1) = (6,6) and (x2,y2) = (h,0).
Slope of BC:
(x1,y1) = (h,0) and (x2,y2) = (0,k).
Now,
Slope of AB = slope of BC
Hope this helps!
Answered by
19
ANSWER✔
✯.FORMULA IN USE ,
✯SIDE AB,
✯SIDE BC
p
✯SIDE AC,
NOW,
SIDE AB = SIDE BC
______________________________
Similar questions